Response of Elevated Water Tanks Subjected to Lateral Loads - Kaul, Matresh; Nallasivan, K. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During previous earthquakes around the world, it was discovered that elevated water tanks were severely damaged or collapsed. As a result, structural engineers are concerned about the analysis of these structures to gain a better understanding of the effects of seismic loads on elevated water tanks. In the current study, E-Tabs software, which is based on finite elements, is used to model various shapes of elevated water tanks along with various staging patterns.
Keywords: water tanks; raising tanks; seismic load; equivalent static method; zbiorniki na wodę; podwyższanie zbiorników; obciążenie sejsmiczne; równoważna metoda statyczna; E-Tabs model